Combination of Microwave-Assisted Girard Derivatization with Ionic Liquid Matrix for Sensitive MALDI-TOF MS Analysis of Human Serum N-Glycans - Hoa Thi Le; Kyu H. Park; Woong Jung; Hyung Soon Park; Tae Woo Kim (Journal of Analytical Methods in Chemistry)
We developed a new method for MALDI-TOF MS detection of N-glycans derived from human serum. The synergistic combination of microwave-assisted Girard T derivatization, solid-phase extraction desalting, and an ionic liquid matrix (2, 5-dihydroxybenzoic acid/aniline) (GT-SPE-DHB/An) allowed of more sensitive N-glycans detection than a conventional ionic liquid matrix in MALDI-TOF MS. The superior sensitivity of our method was confirmed by the number of assigned N-glycans in 900–2,000 m/z range. Using our GT-SPE-DHB/An method, we were successfully able to assign 31 glycans. However, with the established method, i.e., DHB/An method, only 15 glycans were assigned. To the best of our knowledge, this GT-SPE-DHB/An method is the first to combine cationic derivatization of N-glycan and ionic liquid matrix for N-glycan analysis in MALDI-TOF MS.